Detection of Cyberbullying using Machine Learning - et. al., Rupesh Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
It's virtually not possible to measures the reasons why cybersecurity is crucial in the expanding battlefield of cybersecurity. Permitting mischievous threats to operate amok anywhere, whenever, and in any circumstance is not acceptable, particularly when it comes to the complex network of client and organization data that cyber security teams are tasked with safeguarding. Individuals and families, as well as corporations, agencies, and educational institutions, must consider cyber security. Machine Learning Can Help Advance the Cyber Security Landscape. Today's businesses collect massive quantities of information/data. Data is considered as the heart of almost every business-focused system imaginable. Infrastructure systems are included in this. In today’s era high-tech structure, network and cybersecurity systems, collects massive quantities of data and analytics on most mission-critical systems' key elements. While humans also provide critical serviceable oversight and brilliant insights in today's infrastructure, machine learning and artificial intelligence are rapidly gaining traction in almost all domain of today's systems, be it on premises or on the cloud.